Issues of Swine Breeding Development and the Main Solution Ways in the Republic of Armenia - Aleksanyan, V. S.; Mnatsakanyan, K. P.; Orekhova, A. I.; Chmil, A. S. (ՀԱԱՀ հիմնադրամ)
Within the frame of the current scientific article the production and economic indicators of the swine breeding branch in the economy of Armenia have been analyzed. The strategic role and significance of the branch development have been justified putting stress on the increase of self-sufficiecy level of the pork production in the republic. In the mentioned context the disclosure of the issues existing in the swine breeding branch of the RA has been considered as a priority, the solution of which will enable to increase the self-sufficiency level of pork in the country ensuring growth in the consumption sizes of the local pork production, as well as increase in the share of the local production within the overall structure of pork consumption.
Keywords: Agricultural Economics and Agribusiness